(untitled) (Journal of Parents and Teachers, 2024)
The article compares an educational center to an ecosystem, highlighting certain aspects that need to be considered, such as a theoretical synthesis or even a new interdisciplinary methodology. To achieve this, it is essential to embrace a new paradigm, recognizing that educators are working with citizens.